Polyester film

By using ethylene glycol and naphthalene dicarboxylic acid units derived from biomass raw materials in the polyester film, the shortcomings in the existing polyester films in terms of heat resistance and mechanical properties are solved, and a high-performance and environmentally friendly polyester film is achieved.

CN119907821APending Publication Date: 2025-04-29TOYOBO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380067577.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-13
Filing Date
2023-10-10
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing polyester films are difficult to meet the needs in applications requiring high heat resistance and mechanical properties.

Method used

A polyester film containing ethylene glycol units and naphthalene dicarboxylic acid units derived from biomass raw materials is used to improve the heat resistance and mechanical properties of the film by adjusting the proportion and process of the unit.

Benefits of technology

It realizes a polyester film that takes into account environmentally friendly biomass components and high-level characteristics, and is suitable for a variety of uses such as electrical insulation, flexible circuit boards and fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005320845930000251
    Figure BDA0005320845930000251
  • Figure BDA0005320845930000271
    Figure BDA0005320845930000271
  • Figure BDA0005320845930000291
    Figure BDA0005320845930000291
Patent Text Reader

Abstract

Provided is a polyester film which contains a biomass starting material-derived component having a small environmental burden and which can achieve various characteristics at a high level. As the polyester film, disclosed is a polyester film containing a polyester having a diol unit including an ethylene glycol unit derived from a biomass raw material, and a dicarboxylic acid unit including a naphthalene dicarboxylic acid unit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to ester films. Background Art

[0002] Polyester films, particularly films such as polyethylene terephthalate and polyethylene naphthalate, have excellent mechanical properties, heat resistance, and chemical resistance, and are therefore widely used as various raw materials.

[0003] In recent years, various attempts have been made to synthesize polyesters in large quantities from renewable biomass resources. For example, there are reports on polyethylene terephthalate (PET) using ethylene glycol derived from biomass resources as a raw material (Patent Document 1) and polyesters using 1,3-propylene glycol and 1,4-butanediol derived from biomass resources as raw materials (Patent Document 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2013 / 035559

[0007] Patent Document 2: International Publication No. 2012 / 115084 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] However, the polyesters reported in Patent Documents 1 and 2 have difficulty in achieving the required levels for applications requiring, for example, high heat resistance and mechanical properties.

[0010] A main object of the present invention is to provide a polyester film which can contain a component derived from a biomass raw material with a small environmental load and can achieve various properties at a high level.

[0011] Solutions for solving problems

[0012] The present inventors have conducted intensive research to achieve the above-mentioned purpose, and as a result, have found that a polyester film containing a polyester having a diol unit including an ethylene glycol unit derived from a biomass raw material and a dicarboxylic acid unit including a naphthalene dicarboxylic acid unit can achieve various properties at a high level. Based on this finding, the present inventors have repeatedly conducted further intensive research and have thus completed the present invention.

[0013] The present invention includes the following aspects.

[0014] [Item 1]

[0015] A polyester film contains a polyester having a diol unit including an ethylene glycol unit derived from a biomass raw material and a dicarboxylic acid unit including a naphthalene dicarboxylic acid unit.

[0016] [Item 2]

[0017] The polyester film according to Item 1, wherein the polyester accounts for 1 to 100% by mass of all the resins contained in the polyester film.

[0018] [Item 3]

[0019] The polyester film according to item 1 or 2, which is stretched in at least one direction.

[0020] [Item 4]

[0021] The polyester film according to Item 1 or 2, which is used for any one of the following (1) to (13).

[0022] (1) Film for electrical insulation

[0023] (2) Flexible circuit boards

[0024] (3) Flexible circuit board cover film

[0025] (4) Film capacitors

[0026] (5) Polarizer protective film

[0027] (6) Surface protection films for displays

[0028] (7) High barrier substrate

[0029] (8) Films for foldable displays

[0030] (9) Insulation film for motors

[0031] (10) Membrane touch switch substrate

[0032] (11) Gaskets for fuel cells

[0033] (12) Magnetic tape substrate

[0034] (13) Decorative film

[0035] Effects of the Invention

[0036] According to the present invention, a polyester film can be realized which can contain a component derived from a biomass raw material with a small environmental load and can achieve various high-level properties, and can provide a polyester film suitable for the following various uses.

[0037] (1) Film for electrical insulation

[0038] (2) Flexible circuit boards

[0039] (3) Flexible circuit board cover film

[0040] (4) Film capacitors

[0041] (5) Polarizer protective film

[0042] (6) Surface protection films for displays

[0043] (7) High barrier substrate

[0044] (8) Films for foldable displays

[0045] (9) Insulation film for motors

[0046] (10) Membrane touch switch substrate

[0047] (11) Gaskets for fuel cells

[0048] (12) Magnetic tape substrate

[0049] (13) Decorative film BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is a schematic diagram for explaining the method of measuring the holding angle in the bending direction.

[0051] Figure 2 This is an enlarged schematic diagram of a sample film sandwiched between two PTFE plates. DETAILED DESCRIPTION

[0052] Hereinafter, representative embodiments of the present invention will be described in detail.

[0053] The polyester film of the present invention is characterized by containing a polyester (hereinafter sometimes referred to as "bio-PEN") having a diol unit including an ethylene glycol unit derived from a biomass raw material and a dicarboxylic acid unit including a naphthalene dicarboxylic acid unit.

[0054] In this specification, biomass refers to organic resources derived from organisms such as plants and animals, and excludes fossil resources. As biomass, for example, waste resources, unused resources, production resources, etc. can be cited. As waste resources, for example, livestock excrement, food waste, waste paper, black liquor (pulp mill waste liquid), sewage sludge, fecal sludge, wood produced by construction, wood processing factory residues, etc. can be cited. As unused resources, for example, rice straw, wheat straw, rice husk, bagasse, woodland residues, etc. can be cited. As production resources, for example, sugar resources such as sugarcane, starch resources such as corn, oil resources such as palm oil and rapeseed oil, willow, poplar, switchgrass, etc. can be cited.

[0055] The diol unit of bio-PEN is derived from a diol component comprising ethylene glycol derived from biomass raw materials. Ethylene glycol derived from biomass raw materials is, for example, preferably manufactured from ethanol (biomass ethanol) produced using biomass as raw material. In one embodiment, biomass is preferably a sugar resource such as sugar cane. For example, by making biomass ethanol generate ethylene glycol via ethylene oxide according to a method known in the past, ethylene glycol derived from biomass raw materials can be obtained. In addition, commercially available ethylene glycol derived from biomass raw materials can also be used, for example, commercially available ethylene glycol derived from biomass raw materials such as India Glycols Ltd. and Taiwan Green Alcohol Company can be used.

[0056] The diol component is not particularly limited as long as it contains ethylene glycol derived from biomass raw materials. For example, the ethylene glycol in the diol component may be only ethylene glycol derived from biomass raw materials, or may be a combination of ethylene glycol derived from biomass raw materials and ethylene glycol derived from fossil raw materials. In addition, the diol component may also contain diol components other than ethylene glycol. As diol components other than ethylene glycol, for example, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,4-cyclohexanediol, 1,6-hexanediol, dimer glycol, combinations of two or more of these, etc. can be cited.

[0057] The content of ethylene glycol derived from biomass raw materials in the diol component is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 90 mol% or more, and further more preferably 95 mol% or more. The content may be, for example, 100 mol% or less, 99.9 mol% or less, 99.5 mol% or less, or 99 mol% or less. The content may be, for example, in the range of 80 to 100 mol%.

[0058] The dicarboxylic acid unit of bio-PEN is derived from a dicarboxylic acid component including naphthalene dicarboxylic acid and / or its ester-forming derivatives. Naphthalene dicarboxylic acid includes isomers such as 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, and 1,6-naphthalene dicarboxylic acid. From the viewpoint of characteristics and cost when forming a polymer, it is preferred to use 2,6-naphthalene dicarboxylic acid and / or its ester-forming derivatives. The dicarboxylic acid component may also include dicarboxylic acid components other than naphthalene dicarboxylic acid and its ester-forming derivatives. Examples of dicarboxylic acid components other than naphthalene dicarboxylic acid and its ester-forming derivatives include terephthalic acid, isophthalic acid, 4,4'-diphenyl dicarboxylic acid, adipic acid, sebacic acid, dimer acid, their ester-forming derivatives, and combinations of two or more of these. In this specification, an ester-forming derivative refers to a lower alkyl ester (lower alkyl is C 1-6 The alkyl group may be substituted with any substituent such as an alkyl group, or a hydroxyl group), anhydride, halide (e.g., chloride), etc., and methyl ester, ethyl ester, hydroxyethyl ester, etc. are preferably used.

[0059] The content of naphthalene dicarboxylic acid and / or its ester-forming derivative in the dicarboxylic acid component is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 90 mol% or more, and further more preferably 95 mol% or more. The content may be, for example, 100 mol% or less, 99.9 mol% or less, 99.5 mol% or less, or 99 mol% or less. The content may be, for example, in the range of 80 to 100 mol%.

[0060] In one embodiment, the bio-PEN is preferably a polyester having an ethylene glycol unit and a 2,6-naphthalene dicarboxylic acid unit derived from a biomass raw material (hereinafter, sometimes referred to as "bio-2,6-PEN").

[0061] The polyester film of the present invention may further include resins other than bio-PEN. As resins other than bio-PEN, for example, polyesters other than bio-PEN, olefin resins, acrylic resins, styrene resins, polycarbonate resins, polyurethane resins, epoxy resins, combinations of two or more of these, etc., can be cited. Among these, polyesters other than bio-PEN are preferred. As polyesters other than bio-PEN, for example, polyesters (PEN), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polybutylene naphthalate (PBN), polytrimethylene terephthalate (PPT), etc., having ethylene glycol units and naphthalene dicarboxylic acid units without ethylene glycol derived from biomass raw materials can be cited. Among these, PEN other than bio-PEN, for example, PEN derived only from fossil raw materials (hereinafter, sometimes referred to as "PEN derived from fossil raw materials"), etc., can be used.

[0062] The proportion of bio-PEN (especially bio-2,6-PEN) in all the resins contained in the polyester film of the present invention is preferably 1 to 100% by mass. It should be noted that in this specification, "A to B" means A or more and B or less. The proportion is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more. In addition, the proportion can be, for example, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, or 80% by mass or more. Furthermore, the proportion can be, for example, 99% by mass or less, 95% by mass or less, or 90% by mass or less. In the case where the polyester film of the present invention contains bio-PEN and, depending on the circumstances, PEN derived from fossil raw materials, the proportion of bio-PEN relative to the total of bio-PEN and PEN derived from fossil raw materials can be selected from the same range as above (e.g., 1 to 100% by mass).

[0063] In this specification, biomass degree is defined as an index indicating how much of the components constituting a polymer are derived from biomass raw materials. That is, biomass degree refers to the mass ratio of components derived from biomass raw materials in the components constituting a polymer. For example, when 100% of ethylene glycol derived from biomass raw materials is used as a diol component and 100% of naphthalene dicarboxylic acid derived from fossil raw materials is used as a dicarboxylic acid component, the molecular weight of each monomer unit when forming polyester is calculated as follows.

[0064] {(molecular weight of ethylene glycol unit 60×100%)+(molecular weight of naphthalene dicarboxylic acid unit 182*0%)} / (60+182)*100=24.8%

[0065] The biomass degree of the whole resin is the mass ratio of the components derived from the biomass raw materials in the whole resin. For example, when the whole resin is formed by mixing equal amounts of bio-PEN with a biomass degree of 24.8% and a resin with a biomass degree of 0%, the biomass degree of the resin is 12.4%. The biomass degree of the whole resin is preferably 0.2 to 100%, more preferably 1 to 100%, and particularly preferably 5 to 100%.

[0066] In the manufacture of the polyester film of the present invention, the intrinsic viscosity of at least one resin pellet is preferably in the range of 0.4 to 1 dl / g. If the intrinsic viscosity is 0.4 dl / g or more, the impact resistance of the obtained film is improved, and the disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferred. On the other hand, if the intrinsic viscosity is 1 dl / g or less, the filter pressure of the molten fluid will not increase excessively, and the film manufacture can be easily and stably operated, which is preferred.

[0067] For example, the intrinsic viscosity of at least one resin pellet may be 0.5 to 0.8 dl / g, or 0.55 to 0.7 dl / g.

[0068] The polyester film of the present invention may also contain a reused polymer obtained by crushing, drying, and melt-extruding a used film (e.g., a polyester film containing bio-PEN) or a film portion that cannot be commercialized in a film-making process. By containing a reused polymer, the environmental load can be further reduced, so it is preferred. The proportion of the reused polymer in all the resins contained in the polyester film of the present invention may be, for example, 70% by mass or less, 65% by mass or less, 60% by mass or less, 55% by mass or less, or 50% by mass or less. The proportion may be, for example, 1% by mass or more, 5% by mass or more, or 10% by mass or more.

[0069] The thickness of the polyester film of the present invention is preferably 1 μm or more and less than 300 μm, and more preferably 3 μm or more and 275 μm or less. If the thickness is 1 μm or more, the occurrence of cracks during film formation can be prevented, and if the thickness is 300 μm or less, the thickness unevenness is excellent. The thickness can be measured, for example, according to the method described in the examples described later.

[0070] For the polyester film of the present invention, in order to improve the operability, inactive particles can be contained in the polyester. The inactive particles can also be contained in the bio-PEN, but are preferably contained in the polyester other than the bio-PEN. The inactive particles can be inorganic particles or organic particles. As inorganic particles, for example, spherical silica, aluminum silicate particles, titanium dioxide particles, calcium carbonate particles, aggregated silica particles, etc. can be cited. As organic particles, for example, cross-linked polystyrene resin particles, cross-linked silicone resin particles, cross-linked acrylic resin particles, cross-linked styrene-acrylic resin particles, cross-linked polyester particles, polyimide particles, melamine resin particles, etc. can be cited. The inactive particles can be used alone or in combination of two or more.

[0071] The average particle size of the inactive particles is preferably 0.01 μm to 3 μm, more preferably 0.05 μm to 2 μm, and particularly preferably 0.1 μm to 1.5 μm. The average particle size can be measured, for example, by the method described in Examples below.

[0072] There are various methods for adding inactive particles to the resin, such as adding particles to a part of the components constituting the resin to form a slurry and directly polymerizing it, and adding the particles using a twin-screw extruder after the resin is polymerized. Any method can be used. The preferred amount of inactive particles added is 0.001% to 2% relative to the total film mass, more preferably 0.01% to 1%, and particularly preferably 0.1% to 0.8%.

[0073] When a hard coat layer or the like is provided on the polyester film of the present invention, the surface of the polyester film may be subjected to a treatment for improving adhesion with a resin forming the hard coat layer or the like.

[0074] Examples of the surface treatment method include sandblasting, roughening treatment by solvent treatment, corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone / ultraviolet irradiation treatment, flame treatment, chromic acid treatment, and oxidation treatment such as hot air treatment, and the like can be used without particular limitation.

[0075] By sandwiching an adhesion-improving layer such as an easy-adhesive layer between the polyester film of the present invention, the adhesion with the hard coating layer and the like can also be improved. As the easy-adhesive layer, for example, acrylic resins, polyester resins, polyurethane resins, polyether resins, etc. can be used without particular limitation. The easy-adhesive layer can be formed by a general coating method, preferably a so-called online coating prescription. Regarding display applications, especially applications requiring high transparency, the following method is generally adopted: a coating layer is provided on the surface of the film without adding active particles in the polyester resin, and inactive particles are contained in the layer to improve operability.

[0076] The layer structure of the polyester film of the present invention may be a single layer or a laminated structure of two or more layers depending on the application, and is not limited.

[0077] The polyester film of the present invention is preferably stretched in at least one direction.

[0078] The method for producing the polyester film of the present invention can adopt a method known per se. The polyester film of the present invention can be produced, for example, as follows: a resin composition is formed into a film, wherein the resin composition contains a polyester (bio-PEN) obtained by polymerization of a diol component containing ethylene glycol derived from a biomass raw material and a dicarboxylic acid component containing naphthalene dicarboxylic acid and / or its ester-forming derivatives. Specifically, the polyester film of the present invention can be produced, for example, by a method comprising the following steps: step A, using a single extruder, extruding a resin composition containing bio-PEN from a die into a sheet, or using two or more extruders to laminate a resin composition containing bio-PEN and a resin composition different from it in a molten state and then extruding it from a die into a sheet, and cooling and solidifying the obtained sheet, thereby forming a single-layer or laminated unstretched polyester film; step B, stretching the aforementioned unstretched polyester film as needed (preferably stretching in a single direction or orthogonal bidirectional directions); and step C, further heat-treating the stretched polyester film as needed.

[0079] In step A, the temperature when extruding in a molten state is not particularly limited as long as there is no unmelted material and the thermal degradation of the resin does not proceed excessively. For example, it is preferably carried out at a temperature of the melting point (Tm: ° C) of the resin or even (Tm + 70) ° C. In one embodiment, the temperature is preferably 270 to 340 ° C. In addition, regarding cooling, in order to maintain the flatness of the obtained unstretched polyester film and also reduce the thickness unevenness, it is preferred to use a rotating cooling drum arranged below the die head along the film forming direction, so that the sheet is closely attached thereto and cooled. The cooling temperature is preferably carried out at a temperature of (Tg-80) ° C to (Tg-60 ° C) relative to the glass transition temperature (Tg: ° C) of the resin, and in one embodiment, it is preferably 40 to 60 ° C.

[0080] Step B is preferred in terms of being able to produce a polyester film having a desired thickness and Young's modulus and exhibiting better processability at high temperatures. The stretching method includes longitudinal uniaxial stretching, transverse uniaxial stretching, sequential biaxial stretching, and simultaneous biaxial stretching, and there are no particular restrictions. Longitudinal uniaxial stretching is a method in which transverse stretching is omitted from sequential biaxial stretching, transverse uniaxial stretching is a method in which longitudinal stretching is omitted from sequential biaxial stretching, and simultaneous biaxial stretching is a method in which longitudinal and transverse stretching are performed simultaneously. In sequential biaxial stretching, it is preferred that the glass transition temperature of the resin is set to Tg, and the unstretched polyester film is stretched in a uniaxial direction (usually longitudinally) at a temperature of (Tg-10)°C to (Tg+60)°C at a ratio of 1.2 times or more, preferably 1.4 times or more, and then, in a direction orthogonal to the above-mentioned stretching direction, at a temperature of Tg to (Tg+60)°C at a ratio of 2 times or more, preferably 2.5 times or more. It may also be further stretched again in the longitudinal direction and / or transverse direction as needed.

[0081] In step C, the stretched polyester film is preferably heat-treated (heat-set) at a temperature of (Tm-90)°C to (Tm-10)°C, with the melting point of the resin being Tm. In one embodiment, the heat treatment temperature (heat-setting temperature) is preferably 180 to 260°C. The heat-setting time is preferably 0.1 to 60 seconds.

[0082] In the present invention, in order to improve the adhesion between the polyester film and the hard coat layer or the like, or to improve the handling properties, it is also preferred that a coating layer is laminated on at least one surface of the polyester film of the present invention.

[0083] As the resin contained in the coating liquid used in the coating layer, for example, polyester resins, polyurethane resins (for example, polyether polyurethane resins, polyester polyurethane resins, polycarbonate polyurethane resins), acrylic resins, etc. can be used without particular limitation. As the cross-linking agent contained in the coating liquid, for example, melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. can be cited. The cross-linking agent can be used alone or in combination of two or more. In terms of the properties of the online coating, it is preferably coated with an aqueous coating liquid, and the aforementioned resin and cross-linking agent are preferably water-soluble or water-dispersible resins and compounds.

[0084] In order to give the coating layer easy sliding property, it is preferred to add particles. From the aspect of inhibiting the coating layer from falling off, the average particle size of the particles is preferably less than 2 μm. The particles contained in the coating layer can be inorganic particles or organic particles. As inorganic particles, for example, titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, etc. can be cited. As organic particles, for example, organic polymer particles of styrene, acrylic acid, melamine, benzoguanamine, silicone, etc. can be cited. Particles can be added to the coating layer alone, or two or more kinds can be added to the coating layer in combination.

[0085] As a method for applying the coating liquid, a known method can be used, for example, reverse roll coating, gravure coating, kiss coating, roller brushing, spraying, air knife coating, wire rod coating, tubular doctor blade method, etc., which can be carried out alone or in combination.

[0086] The coating layer is preferably formed, for example, by applying a coating liquid for forming the coating layer to one or both sides of an unstretched or longitudinally uniaxially stretched film, and then heat-treating and drying the film as required. The film can be further stretched in at least one direction and heat-treated after stretching to form the coating layer.

[0087] The polyester film containing bio-PEN of the present invention exhibits excellent properties in terms of heat resistance, mechanical properties, and electrical properties, similarly to the polyester film containing PEN derived from fossil raw materials.

[0088] The polyester film of the present invention is suitable for various parts such as surface protection films, polarizing plates, phase difference plates, touch panel substrates, substrates of display units such as organic EL, and protective components on the back. In particular, it is not easy to cause deformation after repeated folding in high temperature areas, and the image distortion at the folded part of the display can be suppressed. Therefore, it can be suitable for use as a film for folding displays. The polyester film of the present invention is suitable for various parts such as surface protection films, polarizing plates, phase difference plates, touch panel substrates, substrates of display units such as organic EL, and protective components on the back in folding displays. A mobile terminal device equipped with a folding display including a polyester film of the present invention provides exquisite images, rich functionality, and excellent convenience such as mobility. The polyester film of the present invention for this purpose is preferably 10 μm or more and 125 μm or less in thickness, 85% or more in total light transmittance, and 60° or more in the bending direction. Here, the high temperature holding angle refers to the angle of the crease brought after being fixed at 85°C for 18 hours in a manner that applies 1.7% strain to each of the two surfaces of the bending part. In addition, the bending direction refers to the direction orthogonal to the folding portion. The high temperature maintenance angle in the bending direction is preferably 65° or more, and more preferably 70° or more. The higher the high temperature maintenance angle in the bending direction, the better, and 180° is most preferred, but it can also be 180° or less, for example, 170° or less also has sufficient function. By making the high temperature maintenance angle in the bending direction within the above range, deformation in high temperature areas such as 85°C can be suppressed. The total light transmittance and the high temperature maintenance angle in the bending direction can be measured, for example, according to the method described in the embodiments described later.

[0089] The polyester film of the present invention can achieve a high elastic modulus and has excellent operability when formed into a film. For example, the moisture expansion coefficient in the width direction, which is important when forming a magnetic tape substrate, can be reduced. Therefore, the polyester film of the present invention can be suitably used for a magnetic tape substrate. From the perspective of excellent dimensional stability, the moisture expansion coefficient (αh) in the width direction of the polyester film of the present invention is preferably 6 ppm / %RH or less (for example, 4 ppm / %RH or more and 6 ppm / %RH or less). The moisture expansion coefficient in the width direction can be measured, for example, according to the method described in the examples described later.

[0090] The polyester film of the present invention has excellent heat resistance and high dielectric breakdown voltage, and therefore can be suitably used as an electrical insulating film. The polyester film of the present invention can also be suitably used in applications such as slot bushings and wedges of automotive drive motors.

[0091] The polyester film of the present invention can increase the anisotropy (retardation) of the in-plane refractive index and can be used as a polarizing plate that does not produce rainbow spots when the polarizing plate protective film as a thin film is mounted on a liquid crystal display device. The preferred film thickness range for this use is 25 to 50 μm, more preferably 30 to 45 μm.

[0092] The polyester film of the present invention is excellent in hot water resistance, has a small oxygen permeability coefficient, and has sufficient vibration durability as a reinforcing member of a polymer electrolyte membrane of a solid polymer electrolyte fuel cell, and can therefore be suitably used as the reinforcing material.

[0093] The polyester film of the present invention has excellent hot water resistance at high temperatures and a small oxygen permeability coefficient, so that when used as an electrolyte membrane reinforcement material for a solid polymer electrolyte fuel cell, it can maintain airtightness. Therefore, it is suitable for use as a film for reinforcing the electrolyte membrane of a solid polymer electrolyte fuel cell.

[0094] The polyester film of the present invention has a small curl value when heated, so it is easy to maintain flatness in the processing step of a membrane touch switch. In addition, it has excellent durability at high temperatures when used as the switch, so it can be particularly suitable for use as a membrane touch switch for automobiles.

[0095] The polyester film of the present invention has a high glass transition temperature. After being bonded to a decorative paint substitute film steel plate and subjected to sharp mechanical stimulation, even if cracks occur in the paint substitute film itself, it is not easy for rust to form on the metal component starting from this crack. Furthermore, the polyester film has a high rust resistance that prevents rust from spreading to the peripheral parts. Therefore, it can be suitably used for automobile exterior parts and the like.

[0096] The polyester film of the present invention has an extremely small heat shrinkage rate and can therefore be suitably used as a film for a flexible circuit board having excellent connection reliability of through holes.

[0097] The polyester film of the present invention has high dielectric breakdown voltage and low dielectric loss tangent characteristics at high temperatures and can be made thinner. Therefore, it can be suitably used as a film for film capacitors with a film thickness of 1 to 5 μm.

[0098] The polyester film of the present invention has excellent gas barrier properties and can therefore be suitably used in applications requiring barrier properties, such as barrier films for protecting organic EL.

[0099] The polyester film of the present invention has properties suitable for any of the following uses (1) to (25), preferably suitable for any of the following uses (1) to (13), and can be suitably used for such uses.

[0100] (1) Film for electrical insulation,

[0101] (2) Flexible circuit boards,

[0102] (3) Flexible circuit board covering film,

[0103] (4) Film capacitors,

[0104] (5) Polarizer protective film,

[0105] (6) Surface protection films for displays,

[0106] (7) High barrier substrate,

[0107] (8) Films for foldable displays,

[0108] (9) Insulating film for motors,

[0109] (10) Thin film touch switch substrate,

[0110] (11) Gaskets for fuel cells,

[0111] (12) Magnetic tape substrate,

[0112] (13) Decorative films,

[0113] (14) Back grinding tape,

[0114] (15) Cutting tape,

[0115] (16) Printed circuit boards,

[0116] (17) Ceramic capacitor release film,

[0117] (18) Release films for laminated electronic substrates,

[0118] (19) Optical films for backlight,

[0119] (20) Brightness improvement film,

[0120] (21) Touch panel substrate,

[0121] (22) Quantum dot substrate film,

[0122] (23) Dimming glass substrate,

[0123] (24) Photo film,

[0124] (25) Film for metal bonding. Specific embodiments

[0126] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited thereto. In the present invention, the properties are measured and evaluated by the following methods.

[0127] (1) Thickness

[0128] The film was measured at 10 locations using a dot-marking electronic micrometer, and the average value was calculated.

[0129] (2) Total light transmittance

[0130] The measurement was conducted using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries, Ltd.).

[0131] (3) 85° holding angle

[0132] The strength of the fold formed when the bent portion was fixed so as to apply a strain of 1.7% to each of the two surfaces was evaluated.

[0133] Figure 1 This is a schematic diagram for illustrating the method of measuring the holding angle in the bending direction. The sample film (symbol 1) is cut to 10 mm in the width direction and 50 mm in the flow direction. Two PTFE plates (symbol 11) are overlapped. In the case of a 50 μm sample film, a 3 mm thick PTFE plate (symbol 12) is sandwiched in the middle as a spacer to form a gap. Double-sided tape is pasted on both ends of the sample, and the 3 mm gap of the PTFE plate is inserted in a bent state, and the two ends are fixed with double-sided tape. After being placed in a dry environment at 85°C for 18 hours, it is taken out from between the two PTFE plates (symbol 11), and the angle of the crease formed on the film is measured after 5 minutes (symbol 13). This angle is used as the high-temperature holding angle.

[0134] Figure 2 An enlarged schematic diagram of a sample film (symbol 3) sandwiched between two PTFE plates (symbol 11 in FIG. 3 ) is shown in FIG. The neutral plane to which neither the compressive stress nor the tensile stress is applied is determined as the center in the thickness direction (dashed line in the figure), and the difference between the neutral plane and the two surfaces is taken as strain.

[0135] It should be noted that Figure 2 In the figure, reference numeral 21 is the diameter of the outermost surface in the sample film, reference numeral 22 is the diameter of the neutral plane in the sample film, and reference numeral 23 is the diameter of the innermost surface in the sample film.

[0136] In the evaluation of the high temperature holding angle, the strain (1.7%) can be expressed by the following method.

[0137] Strain (1.7%) = (|semicircle of the outermost surface or innermost surface - semicircle of the neutral surface| / semicircle of the neutral surface) × 100

[0138] Here, when the thickness of the sample film is t (mm) and the bending diameter (diameter of the outermost surface), that is, the thickness of the spacer used, is d (mm) for the semicircle, they can be respectively calculated by the following formulas.

[0139] The semicircle of the outermost surface = d × π / 2

[0140] The semicircle of the neutral surface = (dt) × π / 2

[0141] The innermost semicircle = (d-2t) × π / 2

[0142] Based on the above, when the strain is set to 1.7%, the thickness of the sample film is set to t (mm), the bending diameter, that is, the thickness of the spacer used is set to d (mm), and the thickness of the spacer used (PTFE plate) is determined by the following formula. The spacer thickness relative to the representative film thickness is shown below.

[0143] Spacer thickness d (mm) = film thickness t (mm) × 60

[0144] For example, in the case of the sample film with a thickness of 50 μm, the diameter of the outermost surface (symbol 21) and the thickness d of the spacer are both 3 mm. The diameter of the innermost surface (symbol 23) is 2.9 mm, and the diameter of the neutral plane (symbol 22) is 2.95 mm. Here, in the formula representing the above strain, the semicircle of the outermost surface and the semicircle of the innermost surface can be appropriately selected.

[0145] (4) Density

[0146] The density was measured by the method according to JIS K 7112:1999 (density gradient tube method). (Unit: g / cm 3 ).

[0147] (5) Thermal shrinkage

[0148] Cut the sample film into 10mm×250mm pieces, mark them at intervals of 200mm along the direction of the long side to be measured, and measure the interval A between the marks under a constant tension of 5g. Next, place the sample film in an oven at a specified temperature for 30 minutes or 10 minutes without load, take it out of the oven, and cool it to room temperature. After that, find the interval B between the marks under a constant tension of 5g, and find the thermal shrinkage (%) according to the following formula. For the same direction, perform 3 measurements, and use the average value as the thermal shrinkage (%).

[0149] Thermal shrinkage (%) = [(AB) × 100] / A

[0150] (6) Elastic modulus

[0151] The film was cut into a sample with a width of 10 mm and a length of 15 cm, and stretched using a universal tensile tester (manufactured by Toyo Baldwin, trade name: TENSILON) at a chuck distance of 100 mm and a stretching speed of 100 mm / min. The elastic modulus was calculated from the slope of the tangent line of the rising portion of the obtained load-elongation curve and the cross-sectional area of ​​the film.

[0152] (7) Coefficient of moisture expansion

[0153] The film was cut into a length of 15 mm and a width of 5 mm in a manner such that the transverse direction of the film became the measurement direction. The length of each sample at a temperature of 30°C, a humidity of 30% RH, and a humidity of 70% RH was measured using a Bruker AXS humidity-controlled thermomechanical analyzer (TMA4000SA, MTC-1000SA), and the moisture expansion coefficient was calculated using the following formula. It should be noted that the measurement direction was the length direction of the cut sample, and the measurement was performed 5 times, with the average value being taken as αh.

[0154] αh=(L70-L30) / (L30×△H)

[0155] Here, L30 in the above formula is the sample length (mm) at 30% RH, L70 is the sample length (mm) at 70% RH, and ΔH: 40 (=70-30)% RH.

[0156] (8) Dielectric breakdown voltage

[0157] The dielectric breakdown voltage was measured by the flat electrode method described in JIS C2151, using ITS-6003 manufactured by Tokyo Seiden Corporation, increasing the voltage at a rate of 1 (KV / sec), and reading the voltage when the film broke with a voltmeter.

[0158] (9) Intrinsic viscosity

[0159] The film or polyester resin is crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution is centrifuged to remove inorganic particles, the flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of only the solvent are measured using an Ubbelohde viscometer. From their time ratio, the intrinsic viscosity is calculated using the Huggins formula, assuming that the Huggins constant is 0.38. Both polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) are evaluated using the same calculation formula.

[0160] (10) Average particle size of particles

[0161] The polyester on the surface layer of the film is removed by low-temperature plasma ashing (e.g., PR-503 manufactured by Yamato Scientific Co., Ltd.) to expose the particles. The treatment conditions are selected so that the polyester is ashed but the particles are not damaged. The particles are observed with a SEM (scanning electron microscope) at a magnification of about 10,000 to 100,000 times, and the area circle equivalent diameter (Di) of at least 1,000 particles is determined by changing the observation position. A particle size distribution curve is prepared, and the mode value is taken as the average particle size. When the particle distribution curve has two or more peaks, the particle size of each peak is taken as the average particle size.

[0162] (11) Refractive index

[0163] The refractive index in the MD direction (Nx), the refractive index in the TD direction (Ny), and the refractive index in the thickness direction (Nz) were measured at a wavelength of 633 nm using a prism coupler Model 2010 / M manufactured by Metricon.

[0164] (12) Birefringence (ΔNxy), retardation (Re)

[0165] The delay amount refers to the phase difference shown by the product of the birefringence generated by the refractive index (Nx, Ny, Nz) of the film in each axial direction and the film thickness d in the thickness direction (z-axis) relative to the film surface and the two axial directions (x-axis and y-axis) that are orthogonal to the thickness direction and also orthogonal to each other. Here, the product of the birefringence Nxy generated by the light incident on the film surface (xy plane) with the MD direction as the x-axis and the TD direction as the y-axis and the thickness d is called the in-plane delay amount, and for each, it is calculated according to the following formula. It should be noted that, according to convention, the unit of delay amount is nm.

[0166] ΔNxy=|Nx-Ny|

[0167] Re=Nxy×d

[0168] (13) Observation of rainbow spots

[0169] The films of the examples and comparative examples prepared by the method described below were attached to one side of a commercially available polarizer so that the absorption axis of the polarizer was perpendicular to the orientation principal axis of the film (the higher of Nx and Ny), and a commercially available TAC film was attached to the opposite surface to prepare a polarizing plate. For this polarizing plate, the polarizing plate on the light-outgoing side of a commercially available liquid crystal display device having a white LED as a backlight and a liquid crystal cell sandwiched between polarizing plates with two TAC films as polarizer protective films was removed, and the films of the examples and comparative examples were set on the light-outgoing side. The liquid crystal display device was visually observed from the front and in an oblique direction, and the occurrence of rainbow spots was determined as follows.

[0170] ○: No rainbow spots occur from any direction

[0171] ×: When observed from an oblique direction, rainbow spots are clearly observed.

[0172] (14) Hot water resistance

[0173] A strip-shaped sample piece of 150 mm long and 10 mm wide was cut with a stainless steel fixture so that the film MD direction became the measurement direction and hung in an environmental tester set to 121°C / 2atm / wet saturation mode / 100%RH. After that, the sample piece was taken out at a predetermined time interval and the breaking strength in the film MD direction was measured. The breaking strength was measured as follows: Using the TENSILONUCT-100 model manufactured by Orientec, in a room adjusted to a temperature of 20°C and a humidity of 50%, the distance between the chucks was 100 mm, and the film was stretched at a stretching speed of 100 mm / min and a recording paper speed of 500 mm / min to obtain the strength at break.

[0174] The measurement was performed 5 times, the average value was calculated, and the time until the breaking strength retention rate in the MD direction represented by the following formula (1) reached 50% of the initial value was calculated to evaluate the hot water resistance. As a measuring device, TENSILONU CT-100 manufactured by Orientec was used.

[0175] Breaking strength retention rate (%) = (breaking strength X / initial breaking strength X0) × 100 (1)

[0176] (In formula (1), the breaking strength X represents the breaking strength (unit: MPa) after treatment under the conditions of 121°C, 2 atm, and 100% RH for a predetermined time, and the breaking strength X0 represents the initial breaking strength (unit: MPa) before treatment.)

[0177] (15) Oxygen permeability coefficient

[0178] The oxygen permeability at 25° C. was measured using an oxygen permeability measuring apparatus (manufactured by Toyo Seiki, MC-1 model) in accordance with JIS K-7126.

[0179] (16) Evaluation of reinforcement performance of reinforced components

[0180] A 100 mm square perfluorosulfonic acid resin (Nafion 117 manufactured by DuPont) was used as an electrolyte membrane, and frame-shaped biaxially oriented films (outer circumference 100 mm×100 mm, inner circumference 80 mm×80 mm) were stacked on both sides and bonded by heat pressing at 140°C.

[0181] The structure of the above-mentioned electrolyte membrane and reinforcement component is fixed on a vibration testing machine, and scanned at an amplitude of 0.75 mm (longitudinal direction), 10 Hz→55 Hz→10 Hz within 60 seconds in an atmosphere of 90°C. This is regarded as one cycle, and the changes in wrinkles, cracks, breakages, etc. of the electrolyte membrane after 10 cycles are visually observed and evaluated using the following criteria.

[0182] ○: No wrinkles, cracks, or breakages were observed in the electrolyte membrane, indicating excellent reinforcement performance

[0183] ×: At least one of wrinkles, cracks, and breaks is observed in part of the electrolyte membrane, and the reinforcing performance is insufficient.

[0184] (17) Heating curling height

[0185] Along the flow direction when manufacturing the film, a film sample of 3 cm × 20 cm in width is placed on an iron plate, and the iron plate is placed in an oven set at 180°C for 5 minutes, then taken out of the oven for natural cooling. Next, the film sample is placed on a glass plate, and the heights of the four corners (vertical direction) are measured to find their average value. The film is turned over and the same measurement is performed, and the larger value is taken as the heat curl height.

[0186] (18) Evaluation of deformation of membrane switches

[0187] Silver paste as a conductive circuit and carbon paste as a printed contact part (electrode) are screen-printed onto a film sample, dried at 140°C for 20 minutes, and after making a switch sheet, a film-like styrene-butadiene resin is used as an adhesive for bonding two sheets together and as a spacer for the film switch.

[0188] The obtained membrane switch was repeatedly subjected to a load (initial load: for example, 1.5 kg / cm 2 ) and the ON / OFF test of removing the load was repeated 10 times to determine the average load (initial load). After that, with the load removed, the membrane switch was placed on an iron plate, and the iron plate was placed in an oven set at 180°C, and taken out after 5 minutes to cool naturally. The load was applied to the switch again, and the ON / OFF test was repeated 10 times to determine the load at which the switch becomes ON (load after treatment). The above test was performed with n=10, and the average value was evaluated according to the following criteria.

[0189] Load change rate (%) = (|load after treatment - initial load| / initial load) × 100

[0190] ○: Change rate is less than 10%, and deformation caused by heat treatment is small

[0191] ×: Change rate exceeds 10%, and deformation due to heat treatment is large

[0192] (19) Evaluation of the rust resistance of decorative coating alternative films

[0193] <Production of decorative coating alternative films>

[0194] First, a coloring layer was applied to the obtained polyester film using a comma coater. The coloring layer used was a solvent coating containing an acrylic urethane resin as a binder component, 20% by mass titanium particles as a pigment, and 35% by mass nonvolatile components. The coating was applied to a thickness of 20 μm, and after drying in a drying oven at 90°C, it was wound up.

[0195] The blank coated with the coloring layer was released again, and then, in order to form a hard coating layer, a hard coating paint (HC-1) described later was applied at 15 μm (thickness after curing) in terms of 30% by mass as a non-volatile component using a comma coater, and then the blank was placed in a drying furnace set at 90° C. and fully dried. Before winding up, a biaxially stretched film formed of a polyethylene terephthalate resin was used as a protective film, laminated, and wound into a roll to obtain a decorative coating alternative film.

[0196] <Hard coating paint (HC-1)>

[0197] In a four-necked flask equipped with a condenser, a stirring device, a thermometer, and a nitrogen inlet tube, 150 parts by mass of methyl isobutyl ketone (MIBK) was added, and the temperature was raised while stirring under a nitrogen atmosphere. After the temperature in the flask reached 74°C, this temperature was used as the synthesis temperature and maintained, and a monomer solution containing 3 parts by mass of methyl methacrylate, 82.54 parts by mass of n-butyl methacrylate, 12.85 parts by mass of 4-hydroxybutyl acrylate, 0.61 parts by mass of methacrylic acid, 1 part by mass of Fancryl FA-711MM (manufactured by Hitachi Chemical Co., Ltd., methacrylic acid-pentamethylpiperidinyl ester), and 0.1 parts by mass of azobisisobutyronitrile was added dropwise over 2 hours. One hour after the monomer addition was completed, azobisisobutyronitrile was added every 1 hour at a rate of 0.02 parts by mass and the reaction was continued until the unreacted monomer in the solution became 1% by mass or less. After the unreacted monomers became less than 1% by mass, the reaction was terminated by cooling to obtain an acrylic copolymer solution having a solid content of about 40% by mass. 59.9 parts by mass (solid mass) of Duranate "P301-75E" (manufactured by Asahi Kasei Chemicals Corporation, a polyisocyanate of hexamethylene diisocyanate, hereinafter referred to as curing agent 1) was added to the acrylic copolymer solution as a polyisocyanate compound, and methyl isobutyl ketone (MIBK) was further added so that the solid content became 30% by mass and stirred to form a hard coating material (HC-1).

[0198] <Production of laminated steel sheets>

[0199] The decorative coating substitute film obtained above was laminated on the plated steel plate JAC270F45 / 45 to produce a laminated steel plate. Specifically, the decorative coating substitute film was unwound (rolled out), the steel plate was heated to 290°C and led out, the laminating roller was kept at room temperature, and the film was laminated by thermal compression bonding under a pressure of 0.3 MPa. The laminated steel plate after lamination was quenched in cooling water to obtain a laminated steel plate.

[0200] <Rust prevention evaluation>

[0201] Two diagonal lines (scratch marks) with a length of 10 cm were drawn on the coating substitute film in the obtained laminated steel plate in such a way that the tip of the cutter reached the base of the steel plate. The laminated steel plate was placed in a cooking kettle, filled with 3% acetic acid + 2% brine, and cooked for 90 minutes under pressurized steam at 125°C. The laminated steel plate was taken out and its state was visually confirmed.

[0202] ○: In all 10 cases, rust occurred only in the scratched portion of the steel plate, but no clear expansion was observed.

[0203] △: In all 10 samples, clear expansion of the rust on the steel plate was observed in any of the samples at the scratch mark.

[0204] ×: In any of the 10 samples, rust was generated in other parts besides the scratch mark, and the film peeled off.

[0205] (20) Thermal cycle evaluation (film for flexible circuit boards)

[0206] <Manufacturing of laminated body>

[0207] At 100°C, a thermosetting adhesive sheet "ARON MIGHTY AF-700" (manufactured by Toagosei Co., Ltd.) was temporarily bonded to both sides of the obtained polyester film, and then a copper foil "TQ-M4-VSP" (manufactured by Mitsui Mining and Smelting Co., Ltd.) with a thickness of 18 μm was overlapped and hot pressed for 30 minutes at 180°C and 1 MPa to produce a flexible copper-clad laminate.

[0208] A through hole with a diameter of 0.1 mm was formed in the obtained copper-clad laminate using a drill, and after the surface was cleaned with acid, the inner surface of the through hole was plated with copper by chemical plating to produce a laminate.

[0209] <Thermal cycle test>

[0210] The laminate obtained above was used to perform a heat cycle test in accordance with the heat shock test method of JIS C5016: 1994. The temperature was set at -55°C to 100°C, the number of cycles was set at 100 times, and the through-hole continuity after the test was evaluated.

[0211] 0: None of the 10 samples had poor conduction.

[0212] ×: One or more of the 10 samples tested had poor conduction.

[0213] (21) Glass transition temperature

[0214] The film was heated from room temperature to a temperature 35°C higher than the melting point of the unstretched film at a heating rate of 20°C / min, melted and held at this temperature for 3 minutes, then taken out and immediately transferred to ice for rapid cooling.

[0215] Then, the temperature is raised again at a rate of 20°C / min to obtain the value in this manner. The Tg reading position is as follows: the temperature at the intersection of the straight line extending from the baseline on the low temperature side to the high temperature side and the tangent line drawn from the point where the gradient of the step portion curve becomes the maximum in the step-shaped change portion of the glass transition of the differential scanning calorimetry graph.

[0216] (22) UV absorption performance

[0217] A polyester film sample of 8 mm in width direction (TD) x 40 mm in machine flow direction (MD) was prepared, and the transmittance at a wavelength of 360 nm was measured using a spectrophotometer (UV1800 manufactured by Shimadzu Corporation) while placing the sample so that the machine flow direction and the gravity direction were parallel.

[0218] (23) Dielectric breakdown voltage (BDV) of capacitor films

[0219] The measurement was performed according to the method described in JIS-C-2318, and the average value of n=100 was defined as the dielectric breakdown voltage (BDV).

[0220] (24) Dielectric loss tangent (tanδ)

[0221] After conditioning the sample film at 23° C. and 50% RH for 16 hours, Al was deposited on both sides of the film, and the values ​​at 100° C. and 1 kHz were measured using electrodes and a capacitance / bridge of JIS-C-2318.

[0222] [Polymerization of PEN resin PEN-1 derived from biomass raw materials]

[0223] Using 0.03 parts by mass of manganese acetate tetrahydrate as an ester exchange catalyst, 60 parts by mass of ethylene glycol (manufactured by India Glycols Ltd.) derived from biomass raw materials and 150 parts by mass of dimethyl 2,6-naphthalenedicarboxylate derived from fossil raw materials were subjected to ester exchange reaction according to a conventional method, and then 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain a polyethylene 2,6-naphthalenedicarboxylate resin having an intrinsic viscosity of 0.62 dl / g. This resin was designated as PEN-1.

[0224] [Polymerization of PEN resin PEN-2 derived from fossil raw materials]

[0225] Using 0.03 parts by mass of manganese acetate tetrahydrate as an ester exchange catalyst, 60 parts by mass of ethylene glycol derived from fossil raw materials and 150 parts by mass of dimethyl 2,6-naphthalenedicarboxylate derived from fossil raw materials were subjected to ester exchange reaction according to a conventional method, and then 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain polyethylene 2,6-naphthalenedicarboxylate resin having an intrinsic viscosity of 0.62 dl / g. This resin was designated as PEN-2.

[0226] [Polymerization of PEN resin (containing lubricant) PEN-3 derived from fossil raw materials]

[0227] Using 0.03 parts by mass of tetrahydrated manganese acetate as an ester exchange catalyst, 150 parts by mass of dimethyl 2,6-naphthalene dicarboxylate derived from fossil raw materials and 60 parts by mass of ethylene glycol derived from fossil raw materials were added in a manner containing 1% by mass of spherical silica particles with an average particle size of 0.3 μm as a lubricant, and after ester exchange reaction according to a conventional method, 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain polyethylene 2,6-naphthalene dicarboxylate resin with an intrinsic viscosity of 0.62 dl / g. This resin was named PEN-3.

[0228] [Polymerization of PEN resin (containing lubricant) PEN-4 derived from fossil raw materials]

[0229] Using 0.03 parts by mass of tetrahydrated manganese acetate as an ester exchange catalyst, 150 parts by mass of dimethyl 2,6-naphthalenedicarboxylate derived from fossil raw materials and 60 parts by mass of ethylene glycol derived from fossil raw materials were added in a manner containing 1% by mass of spherical silica particles with an average particle size of 0.1 μm as a lubricant, and after ester exchange reaction according to a conventional method, 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain polyethylene 2,6-naphthalenedicarboxylate resin with an intrinsic viscosity of 0.62 dl / g. This resin was named PEN-4.

[0230] [Polymerization of PEN resin (containing lubricant) PEN-6 derived from fossil raw materials]

[0231] Using 0.03 parts by mass of manganese acetate tetrahydrate as an ester exchange catalyst, 150 parts by mass of dimethyl 2,6-naphthalenedicarboxylate derived from fossil raw materials and 60 parts by mass of ethylene glycol derived from fossil raw materials were added in a manner containing 1% by mass of calcium carbonate particles with an average particle size of 0.6 μm as a lubricant, and after ester exchange reaction according to a conventional method, 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain polyethylene 2,6-naphthalenedicarboxylate resin with an intrinsic viscosity of 0.62 dl / g. This resin was named PEN-6.

[0232] [Polymerization of PET resin PET-1 derived from biomass raw materials]

[0233] Using 0.03 parts by mass of manganese acetate tetrahydrate as an ester exchange catalyst, 60 parts by mass of ethylene glycol (manufactured by India Glycols Ltd.) derived from biomass raw materials and 100 parts by mass of dimethyl terephthalate derived from fossil raw materials were subjected to ester exchange reaction according to a conventional method, and then 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain a polyethylene terephthalate resin having an intrinsic viscosity of 0.62 dl / g. This resin was designated as PET-1.

[0234] [PET resin PET-2 polymerized from fossil raw materials]

[0235] Using 0.03 parts by mass of manganese acetate tetrahydrate as an ester exchange catalyst, 100 parts by mass of dimethyl terephthalate derived from fossil raw materials and 60 parts by mass of ethylene glycol derived from fossil raw materials were subjected to ester exchange reaction according to a conventional method, and then 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method at high temperature and high vacuum to obtain a polyethylene terephthalate resin having an intrinsic viscosity of 0.62 dl / g. This resin was named PET-2.

[0236] [Polymerization of PET resin (containing lubricant) PET-3 derived from fossil raw materials]

[0237] Using 0.03 parts by mass of tetrahydrated manganese acetate as an ester exchange catalyst, 100 parts by mass of dimethyl terephthalate derived from fossil raw materials and 60 parts by mass of ethylene glycol derived from fossil raw materials were added in a manner containing 1% by mass of spherical silica particles with an average particle size of 0.3 μm as a lubricant, and after ester exchange reaction according to a conventional method, 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain a polyethylene terephthalate resin with an intrinsic viscosity of 0.62 dl / g. This resin was named PET-3.

[0238] [Polymerization of PET resin (containing lubricant) PET-4 derived from fossil raw materials]

[0239] Using 0.03 parts by mass of tetrahydrated manganese acetate as an ester exchange catalyst, 100 parts by mass of dimethyl terephthalate derived from fossil raw materials and 60 parts by mass of ethylene glycol derived from fossil raw materials were added in a manner containing 1% by mass of spherical silica particles with an average particle size of 0.1 μm as a lubricant, and after ester exchange reaction according to a conventional method, 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain a polyethylene terephthalate resin with an intrinsic viscosity of 0.62 dl / g. This resin was referred to as PET-4.

[0240] [Polymerization of PET resin (containing lubricant) PET-5 derived from fossil raw materials]

[0241] Using 0.03 parts by mass of manganese acetate tetrahydrate as an ester exchange catalyst, 100 parts by mass of dimethyl terephthalate derived from fossil raw materials and 60 parts by mass of ethylene glycol derived from fossil raw materials were added in a manner containing 1% by mass of calcium carbonate particles with an average particle size of 0.6 μm as a lubricant, and after ester exchange reaction according to a conventional method, 0.042 parts by mass of triethyl phosphonoacetate was added to substantially terminate the ester exchange reaction. Then, 0.024 parts by mass of antimony trioxide was added, and then polymerization reaction was carried out according to a conventional method under high temperature and high vacuum to obtain a polyethylene terephthalate resin with an intrinsic viscosity of 0.62 dl / g. This resin was named PET-5.

[0242] [Preparation of coating liquid for forming an easily adhesive layer]

[0243] (Polymerization of polyurethane resin)

[0244] In a four-necked flask equipped with a stirrer, a serpentine condenser, a nitrogen inlet tube, a silica gel drying tube and a thermometer, 72.96 parts by mass of 1,3-bis(isocyanatomethyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol with a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as solvents were added, and stirred at 75°C for 3 hours under a nitrogen atmosphere to confirm that the reaction liquid reached the specified amine equivalent. Then, after cooling the reaction liquid to 40°C, 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450 g of water was added to a reaction container equipped with a homodispersor capable of high-speed stirring, and the temperature was adjusted to 25°C. While stirring and mixing at 2000 rpm, the isocyanate group-terminated prepolymer was added to disperse in water. Thereafter, acetonitrile and part of water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35% by mass.

[0245] (Polymerization of water-soluble carbodiimide compounds)

[0246] In a flask equipped with a thermometer, a nitrogen inlet tube, a reflux condenser, a dropping funnel and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phosphorus-1-oxide as a carbodiimidization catalyst were added, and stirred at 180° C. for 10 hours under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Next, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100° C. for 24 hours. Water was slowly added thereto at 50° C. to obtain a yellow transparent water-soluble carbodiimide compound (B) having a solid content of 40% by mass.

[0247] (Preparation of coating liquid for forming an easily adhesive layer)

[0248] The following coating materials were mixed to prepare a coating solution.

[0249]

[0250] [Example 1-1]

[0251] PEN-1 pellets are supplied to the extruder and melted at 300°C. The molten polymer is filtered with a filter material of a stainless steel sintered body (nominal filtration accuracy 10μm particles 95% cutoff), formed into a sheet from a nozzle and extruded, and then cooled and solidified in contact with a casting drum with a surface temperature of 50°C by an electrostatic application casting method to produce an unstretched film. The unstretched film is uniformly heated to 120°C using a heating roller, and the film temperature is heated to 135°C using an infrared heater set between a low-speed roller and a high-speed roller. The speed ratio of the low-speed and high-speed rollers is set to 1.7 times, and the film is stretched in the longitudinal direction to obtain a uniaxially stretched film. Next, the coating amount after drying after biaxial stretching is 0.06g / m by a roller coating method. 2 The coating solution for forming an easy-adhesion layer was applied to both sides of the uniaxially stretched film in a manner. After that, the film was introduced into a tenter, preheated at 145°C, stretched to 4.5 times in the transverse direction at 135°C, fixed in width, heat-set at 230°C for 5 seconds, and further relaxed by 1% in the width direction at 180°C to obtain a polyethylene 2,6-naphthalate film having a thickness of 50 μm. The properties of the film are shown in Table 1.

[0252] [Examples 1-2 and 1-3]

[0253] A polyethylene-2,6-naphthalene dicarboxylate film was obtained in the same manner as in Example 1-1 except that the longitudinal stretching ratio, heat setting temperature, and thickness were as shown in Table 1. Table 1 shows the properties of the film.

[0254] [Comparative Example 1]

[0255] The properties of the film are shown in Table 1.

[0256] [Comparative Example 2]

[0257] PET-1 is mixed in an amount of 79.4 parts by mass and PET-2 is mixed in an amount of 20.6 parts by mass, and the mixture is supplied to an extruder and melted at 285°C. The molten polymer is filtered using a filter material of a stainless steel sintered body (nominal filtration accuracy 10 μm particles 95% cutoff), formed into a sheet from a nozzle and extruded, and then cooled and solidified by contacting with a casting drum having a surface temperature of 30°C using an electrostatic application casting method to prepare an unstretched film. The unstretched film is uniformly heated to 75°C using a heating roller, and the film temperature is heated to 85°C using an infrared heater disposed between a low-speed roller and a high-speed roller. The speed ratio of the low-speed and high-speed rollers is set to 1.4 times, and the film is stretched in the longitudinal direction to obtain a uniaxially stretched film. Next, the film is stretched using a roller coating method to a coating amount of 0.06 g / m after biaxial stretching and drying. 2 The coating solution for forming an easy-adhesion layer was applied to both sides of the uniaxially stretched film in a manner of . After that, the film was introduced into a tenter, preheated at 105°C, stretched to 4.2 times in the transverse direction at 100°C, fixed in width, heat-set at 210°C for 5 seconds, and further relaxed by 1% in the width direction at 130°C to obtain a polyethylene terephthalate film having a thickness of 50 μm. The properties of the film are shown in Table 1.

[0258] [Table 1]

[0259]

[0260] From the comparison between Examples 1-1 to 1-3 and Comparative Examples 1 and 2, it can be seen that the film containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials has a small thermal shrinkage rate, similar to the same film derived from fossil raw materials, and can reduce the dimensional change when the film is used for hard coating processing, etc. In addition, it can be seen that, especially when bent in a high temperature environment, it is difficult to cause creases and it is easy to recover to a shape close to the original shape.

[0261] [Example 2-1 and Comparative Example 3]

[0262] Using the PEN resin shown in Table 2, a film was prepared as follows. The mixed pellets were supplied to an extruder and melted at 300°C. The molten polymer was filtered with a filter material of a stainless steel sintered body (nominal filtration accuracy 10μm particles 95% cutoff), formed into a sheet from a nozzle and extruded, and then, using an electrostatic casting method, contacted with a casting drum with a surface temperature of 50°C to cool and solidify to prepare an unstretched film. The unstretched film was uniformly heated to 120°C using a heating roller, and the film temperature was heated to 140°C using an infrared heater disposed between a low-speed roller and a high-speed roller, and the speed ratio of the low-speed and high-speed rollers was set to 4.0 times, and stretched in the longitudinal direction to obtain a uniaxially stretched film. After that, it was introduced into a tenter, preheated at 130°C, stretched to 5.7 times in the transverse direction at 145°C, fixed in width, heat-set at 210°C for 5 seconds, and further relaxed by 1% in the width direction at 180°C to obtain a polyethylene 2,6-naphthalate film having a thickness of 5 μm. The properties of the film are shown in Table 2.

[0263] [Examples 2-2 and 2-3]

[0264] A polyethylene-2,6-naphthalene dicarboxylate film was obtained in the same manner as in Example 2-1 except that the longitudinal stretching ratio, the transverse stretching ratio, and the thickness were as shown in Table 2. Table 2 shows the properties of the film.

[0265] [Comparative Example 4]

[0266] Using the PET resin shown in Table 2, a film was made as follows. The mixed pellets were supplied to an extruder and melted at 285°C. The molten polymer was filtered with a filter material of a stainless steel sintered body (nominal filtration accuracy 10μm particles 95% cutoff), formed into a sheet from a nozzle and extruded, and then contacted with a casting drum with a surface temperature of 30°C by an electrostatic casting method to cool and solidify to make an unstretched film. The unstretched film was uniformly heated to 75°C using a heating roller, and the film temperature was heated to 85°C using an infrared heater set between a low-speed roller and a high-speed roller. The speed ratio of the low-speed and high-speed rollers was set to 3.2 times, and the film was stretched longitudinally to obtain a uniaxially stretched film. After that, it was introduced into a tenter, preheated at 100°C, stretched transversely to 4.5 times at 110°C, fixed in width, heat set at 210°C for 5 seconds, and further relaxed by 1% at 180°C in the width direction to obtain a polyethylene terephthalate film with a thickness of 5μm. Table 2 shows the properties of the film.

[0267] [Table 2]

[0268]

[0269] Comparison between Examples 2-1 to 2-3 and Comparative Examples 3 and 4 shows that the polyester film of the present invention containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials has a small thermal shrinkage and a large elastic modulus, and is excellent in handling properties, as does a film containing polyethylene 2,6-naphthalene dicarboxylate derived only from fossil raw materials. In addition, when forming a magnetic tape substrate, the moisture expansion coefficient in the width direction, which is particularly important, can also be reduced, as does polyethylene 2,6-naphthalene dicarboxylate derived from fossil raw materials.

[0270] [Example 3-1 and Comparative Example 5]

[0271] Using the PEN resin shown in Table 3, a film was made as follows. The mixed pellets were supplied to an extruder and melted at 315°C. The molten polymer was filtered with a filter material of a stainless steel sintered body (nominal filtration accuracy 10μm particles 95% cutoff), formed into a sheet from a nozzle and extruded, and then, using an electrostatic casting method, contacted with a casting drum with a surface temperature of 50°C to cool and solidify to make an unstretched film. The unstretched film was uniformly heated to 120°C using a heating roller, and the film temperature was heated to 130°C using an infrared heater disposed between a low-speed roller and a high-speed roller. The speed ratio of the low-speed and high-speed rollers was set to 2.9 times, and stretched in the longitudinal direction to obtain a uniaxially stretched film. After that, it was introduced into a tenter, preheated at 120°C, stretched to 2.8 times in the transverse direction at 140°C, fixed in width, heat-set at 235°C for 5 seconds, and further relaxed by 3% in the width direction at 180°C to obtain a polyethylene 2,6-naphthalate film having a thickness of 250 μm. The properties of the film are shown in Table 3.

[0272] [Examples 3-2 and 3-3]

[0273] A polyethylene 2,6-naphthalate film was obtained in the same manner as in Example 3-1 except that the longitudinal stretching ratio, the transverse stretching ratio, the heat setting temperature, and the thickness were set as shown in Table 3. Table 3 shows the properties of the film.

[0274] [Comparative Example 6]

[0275] Using the PET resin shown in Table 3, a film was made as follows. The mixed pellets were supplied to an extruder and melted at 285°C. The molten polymer was filtered with a filter material of a stainless steel sintered body (nominal filtration accuracy 10μm particles 95% cutoff), formed into a sheet from a nozzle and extruded, and then contacted with a casting drum with a surface temperature of 30°C to cool and solidify to make an unstretched film using an electrostatic casting method. The unstretched film was uniformly heated to 75°C using a heating roller, and the film temperature was heated to 85°C using an infrared heater disposed between a low-speed roller and a high-speed roller. The speed ratio of the low-speed and high-speed rollers was set to 2.9 times, and the film was stretched longitudinally to obtain a uniaxially stretched film. After that, it was introduced into a tenter, preheated at 100°C, stretched transversely to 2.8 times at 110°C, fixed in width, heat set at 230°C for 5 seconds, and further relaxed by 1% at 180°C in the width direction to obtain a polyethylene terephthalate film with a thickness of 250μm. Table 3 shows the properties of the film.

[0276] [Example 4]

[0277] The film with a thickness of 250 μm produced in Example 3-1 was crushed and dried, supplied to an extruder, and melted at 310°C. The molten polymer was filtered using a filter material of a stainless steel sintered body (nominal filtration accuracy 10 μm particles 95% cutoff), extruded from a nozzle onto a strand, water-cooled, cut into 5 mm lengths, and recycled pellets were made as PEN-5. PEN-1, PEN-3, and PEN-5 were mixed in the proportions described in Table 3, and then a polyethylene naphthalate film with a thickness of 250 μm was obtained in the same manner as in Example 3-1. The properties of the film are shown in Table 3.

[0278] [Table 3]

[0279]

[0280] As can be clearly seen from the comparison between Examples 3-1 to 3-3 and Comparative Examples 5 and 6, the polyester film of the present invention containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials has a small thermal shrinkage and a large dielectric breakdown voltage, just like the film containing polyethylene 2,6-naphthalene dicarboxylate only derived from fossil raw materials, and is also excellent as an insulating material.

[0281] The film of Example 4 maintains the same biomass degree and film properties as Examples 3-1 to 3-, and on this basis, uses PEN-5 as recycled pellets, thereby greatly reducing the amount of PEN-1 and PEN-3 used, which can greatly reduce the environmental load.

[0282] [Example 5-1 and Comparative Example 7]

[0283] A polyester film having a thickness of 40 μm was obtained in the same manner as in Example 1-1 except that the raw materials, stretch ratio, and heat setting temperature used were as shown in Table 4. Table 4 shows the properties of the obtained film.

[0284] [Examples 5-2 to 5-4]

[0285] A polyethylene 2,6-naphthalate film was obtained in the same manner as in Example 5-1 except that the longitudinal stretching ratio, transverse stretching ratio, heat setting temperature, and thickness were set as shown in Table 3. Table 4 shows the properties of the film.

[0286] [Comparative Example 8]

[0287] A polyester film having a thickness of 40 μm was obtained in the same manner as in Comparative Example 2 except that the raw materials, stretch ratio, and heat setting temperature used were as shown in Table 4. Table 4 shows the properties of the obtained film.

[0288] [Table 4]

[0289]

[0290] As shown by the comparison between Examples 5-1 to 5-4 and Comparative Examples 7 and 8, the polyester film of the present invention containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials can increase the delay amount in the same way as the film containing polyethylene 2,6-naphthalene dicarboxylate only derived from fossil raw materials, and can be incorporated into a display device and used as a polarizing plate protective film without generating rainbow spots.

[0291] [Example 6-1 and Comparative Example 9]

[0292] The raw materials, stretch ratio, heat setting temperature and thickness used were as shown in Table 5. The film was coated with 4 g / m2 on one side of the uniaxially stretched film by a kiss coating method. 2 A polyester film having a thickness of 25 μm was obtained in the same manner as in Example 3-1 except that an aqueous coating liquid B having a solid content concentration of 3 wt% was applied. The properties of the obtained film are shown in Table 5. Coating liquid B was prepared by mixing 10 wt% of polyoxyethylene lauryl ether (n=7) with 90 wt% of an acrylic copolymer composed of 70 mol% of methyl methacrylate / 22 mol% of ethyl acrylate / 4 mol% of N-hydroxymethyl acrylamide / 4 mol% of N,N-dimethyl acrylamide as a solid content.

[0293] [Examples 6-2 and 6-3]

[0294] A polyethylene 2,6-naphthalate film was obtained in the same manner as in Example 6-1 except that the longitudinal stretch ratio, the transverse stretch ratio and the thickness were as shown in Table 5. Table 4 shows the properties of the film.

[0295] [Comparative Example 9]

[0296] The raw materials, stretch ratio, heat setting temperature and thickness used were set as shown in Table 5. In the same manner as in Example 6-1, a kiss coating method was used to coat the film on one side at a temperature of 4 g / m 2 A polyester film having a thickness of 25 μm was obtained in the same manner as in Comparative Example 6 except that the aqueous coating liquid B having a solid content concentration of 3 wt % was applied.

[0297] [Table 5]

[0298]

[0299] As shown in the comparison between Examples 6-1 to 6-3 and Comparative Examples 9 and 10, the polyester film containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials of the present invention has excellent hot water resistance and oxygen barrier properties, as does the film containing polyethylene 2,6-naphthalene dicarboxylate derived from fossil raw materials alone. In addition, when used as a reinforcing member, the vibration durability at high temperature is also excellent. When used as a reinforcing member of a polymer electrolyte membrane of a solid polymer electrolyte fuel cell, the mechanical strength can be maintained for a long time under a high temperature / high humidity use environment, and the confidentiality (airtightness) can be maintained without applying a load to the electrolyte membrane.

[0300] [Example 7-1 and Comparative Example 11]

[0301] A polyester film having a thickness of 125 μm was obtained in the same manner as in Example 3-1 except that the raw materials, stretch ratio, heat setting temperature, and thickness used were as shown in Table 6. Table 6 shows the properties of the obtained film.

[0302] [Examples 7-2 and 7-3]

[0303] A polyethylene 2,6-naphthalate film was obtained in the same manner as in Example 7-1 except that the longitudinal stretch ratio, transverse stretch ratio, heat setting temperature and thickness were as shown in Table 6. The properties of the film are shown in Table 6.

[0304] [Comparative Example 12]

[0305] A polyester film having a thickness of 125 μm was obtained in the same manner as in Comparative Example 6 except that the raw materials, stretch ratio, heat setting temperature, and thickness used were as shown in Table 6. Table 6 shows the properties of the obtained film.

[0306] [Table 6]

[0307]

[0308] As shown by the comparison between Examples 7-1 to 7-3 and Comparative Examples 11 and 12, the polyester film of the present invention containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials is not prone to curling when heated, just like the film containing polyethylene 2,6-naphthalene dicarboxylate only derived from fossil raw materials. In addition, the durability at high temperatures when forming a thin film touch switch is also excellent, and it is particularly useful as a thin film touch switch for automobiles.

[0309] [Example 8-1 and Comparative Example 13]

[0310] A polyester film roll having a thickness of 50 μm was obtained in the same manner as in Example 3-1 except that the raw materials, stretch ratio, heat setting temperature, and thickness used were as shown in Table 7. Table 7 shows the properties of the obtained film.

[0311] [Examples 8-2 and 8-3]

[0312] A polyethylene 2,6-naphthalate film was obtained in the same manner as in Example 8-1 except that the thickness was set as shown in Table 7. Table 7 shows the properties of the film.

[0313] [Comparative Example 14]

[0314] A polyester film roll having a thickness of 50 μm was obtained in the same manner as in Comparative Example 6 except that the raw materials, stretch ratio, heat setting temperature, and thickness used were as shown in Table 7. Table 7 shows the properties of the obtained film.

[0315] [Table 7]

[0316]

[0317] As shown by comparison between Examples 8-1 to 8-3 and Comparative Examples 13 and 14, the polyester film containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials of the present invention is particularly useful as a decorative coating alternative film, similar to the film containing polyethylene 2,6-naphthalene dicarboxylate derived only from fossil raw materials.

[0318] [Examples 9-1 to 9-3 and Comparative Example 15]

[0319] The films obtained in Examples 8-1 to 8-3 and Comparative Example 13 were further subjected to heat treatment at 230° C. for 5 minutes using a drape-type relaxation heat treatment apparatus. Table 8 shows the properties of the obtained films.

[0320] [Table 8]

[0321]

[0322] Table 8 shows that the polyester film of the present invention containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials has an extremely small thermal shrinkage rate, similar to the film containing polyethylene 2,6-naphthalene dicarboxylate only derived from fossil raw materials, and can therefore be suitably used as a film for flexible circuit boards with excellent through-hole connection reliability.

[0323] [Example 10-1 and Comparative Example 16]

[0324] A polyethylene-2,6-naphthalate film having a thickness of 1.5 μm was obtained in the same manner as in Example 3-1 except that the raw materials, stretch ratio, heat setting temperature, and thickness used were as shown in Table 6. Table 6 shows the properties of the obtained film.

[0325] [Examples 10-2 and 10-3]

[0326] A polyethylene-2,6-naphthalene dicarboxylate film was obtained in the same manner as in Example 10-1 except that the heat setting temperature and thickness were set as shown in Table 6. Table 9 shows the properties of the film.

[0327] [Table 9]

[0328]

[0329] Comparison of Examples 10-1 to 10-3 with Comparative Example 16 shows that the polyester film of the present invention containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials has a high dielectric breakdown voltage and a low tanδ value at a high temperature of 100°C, just like a film containing polyethylene 2,6-naphthalene dicarboxylate derived only from fossil raw materials. It has durability and low dielectric loss tangent (tanδ) performance when forming a thin film capacitor, and is particularly useful as a thin film capacitor for high temperature and large capacity applications.

[0330] [Example 11-1 and Comparative Example 17]

[0331] A polyethylene-2,6-naphthalate film having a thickness of 50 μm was obtained in the same manner as in Example 1-1 except that the raw materials, stretch ratio, heat setting temperature, and thickness used were as shown in Table 10. Table 10 shows the properties of the obtained film.

[0332] [Examples 11-2 and 11-3]

[0333] A polyethylene 2,6-naphthalate film was obtained in the same manner as in Example 11-1 except that the longitudinal stretching ratio, transverse stretching ratio, heat setting temperature and thickness were as shown in Table 10. The properties of the film are shown in Table 9.

[0334] [Table 10]

[0335]

[0336] Comparison of Examples 11-1 to 11-3 with Comparative Example 17 shows that the polyester film of the present invention containing polyethylene 2,6-naphthalene dicarboxylate derived from biomass raw materials has low heat shrinkage, excellent dimensional stability, low oxygen permeability, and low UV transmittance at 360 nm, just like the film containing polyethylene 2,6-naphthalene dicarboxylate only derived from fossil raw materials. It is particularly useful as a film requiring barrier properties, especially a barrier film for organic EL, a substrate film for quantum dots, and other uses requiring high barrier properties.

[0337] Industrial Applicability

[0338] The polyester film of the present invention containing polyethylene naphthalate (polyethylene 2,6-naphthalate, etc.) derived from biomass raw materials has extremely excellent thermal properties, mechanical properties and electrical properties, similar to the film containing only polyethylene naphthalate (polyethylene 2,6-naphthalate, etc.) derived from fossil raw materials, and can be usefully used in a wide range of applications such as display devices, automobile applications, and information communications.

[0339] Description of Reference Numerals

[0340] 1: Sample film

[0341] 11: PTFE sheet

[0342] 12: Spacer

[0343] 13: Keep Angle

[0344] 21: The diameter of the outermost surface

[0345] 22: Diameter of the neutral plane

[0346] 23: Diameter of the innermost surface.

Claims

1. A polyester film comprising a polyester having a diol unit including an ethylene glycol unit derived from a biomass raw material and a dicarboxylic acid unit including a naphthalene dicarboxylic acid unit.

2. The polyester film according to claim 1, wherein The polyester accounts for 1 to 100% by mass of all the resins contained in the polyester film. 3 . The polyester film according to claim 1 , which is stretched in at least one direction.

4. The polyester film according to claim 1 or 2, which is used for any one of the following (1) to (13), (1) Film for electrical insulation (2) Flexible circuit boards (3) Flexible circuit board cover film (4) Film capacitors (5) Polarizer protective film (6) Surface protection films for displays (7) High barrier substrate (8) Films for foldable displays (9) Insulation film for motors (10) Membrane touch switch substrate (11) Gaskets for fuel cells (12) Magnetic tape substrate (13) Decorative film.

Citation Information

Patent Citations

  • Diol composition and polyester

    WO2012115084A1

  • Polyester with excellent heat resistance and method for producing same

    WO2013035559A1